Pulmonary Infections in Immunocompromised Hosts: Clinical. Issue 5 (September 2018) - Vazquez Guillamet, Cristina; Hsu, Joe Le; Dhillon, Gundeep; Vazquez Guillamet, Rodrigo
Abstract : Pulmonary infections in immunocompromised patients remain a significant contributor to mortality, morbidity, and health care–associated costs in such a vulnerable patient population. Their epidemiology is changing, set forth by new trends in immunosuppressive regimens and also prophylaxis. The host characteristics, presenting clinical symptomatology, along with radiographic patterns, have also evolved. The microbiology diagnostics are now enriched with nonculture methods for better identification of the causative pathogens. Chest imaging remains the cornerstone of the initial workup. Our article will examine the new trends in epidemiology, clinical findings, and diagnostics for immunocompromised patients with pulmonary infections (transplant recipients, neutropenic hosts, HIV-infected patients, and patients with autoimmune conditions). We will also review the differential diagnosis that most of the times includes malignancies and drug or radiation-related toxicities.